Clinicoepidemilogical Correlation of BRCA 1 and 2 Mutations in Carcinoma Ovary - an Indian Perspective - Rathore, Anvesh; Vishwanath, S; Ranjan, Subhash; Pathak, Abhishek; Dubey, AP; Nikhil, P (Indian Journal of Medical and Paediatric Oncology, 2019)
Introduction: All over the world in 2008, approximately 225,000 women were diagnosed with ovarian cancer, and 140,000 died from this disease.1 Ovarian cancer is the second-most common gynecologic malignancy in the developed countries. In the developing countries, it is the third-most common gynecologic malignancy after breast and cervical cancer with an incidence of 5.0/100,000 and a mortality rate of 3.1/100,000. Women with BRCA1 gene mutations typically develop ovarian cancer at an earlier age than other women, with an average age at diagnosis of 50-year-old while for patients with BRCA2 mutation carriers it is 60 years, similar to the general population. Aim and Objective: The aim of this study is to study the incidence, clinical profile, and outcomes of a patient with BRCA 1 and BRCA 2 mutation in carcinoma ovary and its comparison with patients without mutation. Results: Out of total 50 patients, 45 (90%) were BRCA negative and rest fi ve (10%) were BRCA positive. Of the five patients, only two (4% of total) had pathological mutations while the rest of three patients had benign mutations only. Overall median age of presentation was 61 years for BRCA-negative patients and 38 years for BRCA-positive patients. Most of the patients presented in Stage III (23 out of 50; 46%), while the second-most common presentation was in Stage IV (34%). In our study, we had an overall mortality of one patient who was BRCA negative, in Stage IV while no mortality was noted in BRCA positive subset of patients. Conclusion: This was a single center-based and spanned over 24 months involving limited number of patients with ovarian cancer with maximum follow-up for 9 months.
Keywords: BRCA 1 and 2 mutations; carcinoma ovary; germline mutation